Ovine Pulmonary Adenocarcinoma: A Unique Model to Improve Lung Cancer Research - Gray, Mark E.; Meehan, James; Sullivan, Paul; Marland, Jamie R. K.; Greenhalgh, Stephen N.; Gregson, Rachael; Clutton, Richard Eddie; Ward, Carol; Cousens, Chris; Griffiths, David J.; Murray, Alan; Argyle, David (Frontiers in Oncology, 2019)
Lung cancer represents a major worldwide health concern; although advances in patient management have improved outcomes for some patients, overall 5-year survival rates are only around 15%. In vitro studies and mouse models are commonly used to study lung cancer and their use has increased the molecular understanding of the disease. Unfortunately, mouse models are poor predictors of clinical outcome and seldom mimic advanced stages of the human disease. Animal models that more accurately reflect human disease are required for progress to be made in improving treatment outcomes and prognosis. Similarities in pulmonary anatomy and physiology potentially make sheep better models for studying human lung function and disease. Ovine pulmonary adenocarcinoma (OPA) is a naturally occurring lung cancer that is caused by the jaagsiekte sheep retrovirus. The disease is endemic in many countries throughout the world and has several features in common with human lung adenocarcinomas, including histological classification and activation of common cellular signalling pathways. Here we discuss the in vivo and in vitro OPA models that are currently available and describe the advantages of using pre-clinical naturally occurring OPA cases as a translational animal model for human lung adenocarcinoma. The challenges and options for obtaining these OPA cases for research purposes, along with their use in developing novel techniques for the evaluation of chemotherapeutic agents or for monitoring the tumour microenvironment in response to treatment, are also discussed.